Analisa Komparatif Kinerja Reksadana Pendapatan Tetap Dan Reksadana Terproteksi Berdasarkan Indeks Treynor, Sharpe, Dan Jensen Studi Empiris Tahun 2008-2010 - , Yudhistira, SE. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In taking an investment decision, investors want a lucrative investment and a small level of risk and quick returns. Therefore, there should be an assessment of the performance of mutual funds, so that can know what a mutual funds that has the best investment prospects. This study aims to determine the performance of fixed income mutual funds and protection, using descriptive and inferential statistical research, and data analysis performed by the formula Treynor, Sharpe, and Jensen Measure and use the test paired sample t-test. Elections were conducted on five investment managers with the best ratings, each investment manager established two product types of fixed income mutual funds and protection during the period January 2008 - December 2010 From the calculation has been done based on Sharpe's index and Jensen concluded that the fixed-income mutual funds have performance level better than mutual funds protection, while the Treynor index inferred based on mutual protection fund has a better performance level compared with fixed-income mutual funds. Based on the test of paired samples t-test proved that there is no significant performance differences between methods Treynor, Sharpe, and Jensen.